CASHEW NUT-BASED PRODUCTION SYSTEMS IN TOGO: AGRICULTURAL PRACTICES, CONSTRAINTS, AND IMPROVEMENT LEVERS - Alèdi Assih; Amen Yawo Nenonene (Socio-Economics/Agribusiness Department, 2022)
This research aims to characterize cashew nut production systems in Togo and identify intervention axes to increase productivity. The method is based on a survey of 384 cashew producers in the main production areas. The results showed that 96.5% of the producers are men, and cashew plantations are mostly owned (79.9%) by indigenous peoples. The average age of producers is 48.15±11.60 years, and most farmers (91%) field is less than three (03) hectares. More than 79% of orchards are obtained by directly sowing and are rarely fertilized (6.34%). Intercropping is frequently practiced and lasts on average 5.1±2.2 years. Cashew nut yields are negatively affected by the long duration of intercropping, labor costs, and the long time between two harvests. Three major groups are distinguished among cashew producers, and ease of access to land is the factor that best discriminates them. Cashew nut yields remain low and average 345 kg/ha. Economic and technical constraints remain the main problems encountered in the field. Thus, the levers for improving cashew nut productivity are the strengthening of contract farming, strengthening of extension services and a better organization of the actors of the sector.